Lines on the classification of Ethopian-Semitic - Jack Fellman (Studies in African linguistics, 1996)
Ethiopian-Semitic constitutes a compact, readily defined and homogeneous linguistic family, consisting of Ge' ez, Tigre, Tigrinya, Amharic, Argobba, Harari, Gafat, and the Gurage cluster. The most recent attempt to set up a classification of Ethiopian-Semitic was Hetzron [1972}, but this work was rather thoroughly criticized by Goldenberg [1977], and the field has yet to recover from it. The present note seeks to open the classification question anew by providing a basic, minimalist classification scheme, which can serve as a starting-off point for any future work on the subject. We begin with some of the results of Marcel Cohen [1931], "the father of Ethiopian studies" in the twentieth century. Cohen treats Tigre and Tigrinya as Northern Ethiopic, and Amharic, Harari, and the Gurage cluster as Southern Ethiopic. All are ultimately descendants of a ProtoEthiopic koine most closely resembling Ge'ez. Gurage, according to Cohen, is not a language or a linguistic unit in itself, but rather an ensemble of at least two separate and mutually unintelligible dialect clusters, Eastern Gurage and Western Gurage. Eastern Gurage consists of Wolane, Selti-Ulbarag, (and in the present state of our knowledge also Zway) , and is most closely connected with Harari. Western Gurage consists of several subgroups of dialects, in particular (a) Chaha, Ezha, Ennemor (Inor), Gumar, Gyeto (and in the present state of our knowledge Endegefi) and (b) Muher, Gogot, Masqan. Aymallel (Soddo, Kgstangiiiia), another Gurage tongue, is left unclassified by Cohen, as being perhaps intermediate between the two groups. Tentatively, he terms it North-Eastern Gurage. (Gafat and Argobba are not classified by Cohen.) Cohen's classification may be modified and/or expanded on the basis of the following points. Western Gurage tongue.